Learning Motivation Impact on Social Skills in Elementary Education - Siti Fatimah (CV. Akademi Merdeka, 2024)
Social skills are essential for pupils’ academic success and peer relationships, yet few studies have examined the internal factors that nurture these skills in the cooperative setting of elementary Social Studies (IPS). This study investigates the relationship between learning motivation and social skills among 42 fourth-grade students at a public elementary school. Data were collected using validated questionnaires and analyzed through two complementary methods. Simple linear regression (SPSS v29) was used to assess the direct effect of motivation, yielding a standardized coefficient (β) of 0.408 and an R² of 0.253, indicating that learning motivation explains 25.3% of the variance in students’ social skills, a moderate and meaningful effect. To validate this relationship, Structural Equation Modeling (SEM) using SmartPLS v4.0.9.9 produced a path coefficient of 0.714 (p < 0.001), confirming a strong, statistically significant influence. This study contributes to the growing literature on motivational determinants of student behavior, particularly in Social Studies contexts. The findings offer practical insights for educators, suggesting that integrating student-centered, engaging activities can enhance both motivation and the development of students’ interpersonal competencies.